Different look at the spin state of Co 3+ ions in a CoO 5 pyramidal coordination - Hu, Zhimin; Haverkort, Maurits W. (Physical review letters, 2004)
Using soft-x-ray absorption spectroscopy at the Co L2,3 and O K edges, we demonstrate that the Co3+ ions with the CoO5 pyramidal coordination in the layered Sr2CoO3Cl compound are unambiguously in the high spin state. Our result questions the reliability of the spin state assignments made so far for the recently synthesized layered cobalt perovskites and calls for a reexamination of the modeling for the complex and fascinating properties of these new materials.
Im Titel ist "3+" hoch und "5" tiefgestellt
Gesehen am 08.11.2017